Pendidikan Bisnis untuk Anak Sekolah Dasar - Ari Purwianti; Siti Nur khoiriyah; Rizky Nuryanti; Christian Tjatur; Ludi Wishnu Wardana; Bagus Shandy Narmaditya (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Systematic literature review (SLR) articles on business education for elementary school children have the objective of; (1) Identify factors that can affect the success of students from business education; (2)Integrating proper business education for elementary school students; (3) The implementation of the appropriate curriculum to prepare elementary school students to face future business challenges. The systematic literature review (SLR) article writing method is a literature research method sourced from the Elsevier and Google Schoolar databases. SLR analysis uses the PRISMA method to find relevant articles according to the research objectives. The results of this study found that the success of business education at the elementary school level is influenced by several factors, namely (a) motivational support such as incentives and the role of teachers, (b) development of business attitudes and characters (leadership, creativity, and self-control), as well as mastery of knowledge and practical skills in the simple business world. The implications of this research for the elementary school curriculum are to integrate business education through various projects that can increase students' awareness and business skills.